Putting universities in their place : an evidence-based approach to understanding the contribution of higher education to local and regional development /: an evidence-based approach to understanding the contribution of higher education to local and regional development. (2021) - Kempton, Louise; Conceição Rego, Maria; Reinaldo Alves, Lucir; Vallance, Paul; Aguiar Serra, Maurício; Tewdwr-Jones, Mark
No abstract available